PENGARUH LAYANAN CASH DEPOSIT MACHINE TERHADAP KEPUASAN NASABAH PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. CABANG AHMAD YANI MAKASSAR - Ibrahim Bazergan (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this study is to determine the effect of Cash Deposit Service Machine on Customer Satisfaction At PT. Bank Rakyat Indonesia (Persero) Tbk. Ahmad Yani Makassar Branch. This research was conducted at Branch Office of BRI Makassar, using simple regression analysis method, likert scale, instrument test consisting of validity and reliability test, and partial hypothesis test (t test). The results showed that Cash Deposit Service Service has a positive and significant effect on Customer Satisfaction PT. BRI Branch Ahmad Yani Makassar.